Advances in polysaccharide nanocrystals as pharmaceutical excipients. (15th June 2021) - Si, Yanxue; Luo, Huize; Zhou, Fengshan; Bai, Xinyi; Han, Lu; Sun, Huimin; Cha, Ruitao
Highlights: We summarize the pharmaceutical applications of polysaccharide nanocrystals (PNs). We discuss regulatory issues of PNs as pharmaceutical excipients. We raise challenges and potentials of PNs in pharmaceutical field. Abstract: Polysaccharide nanocrystals (PNs) are attractive pharmaceutical excipients due to their abundant surface hydroxyl groups, high surface charges, prominent mechanical properties, excellent fluidity, and good swelling properties. In this review, we summarize three kinds of PNs, including cellulose nanocrystals (CNCs), starch nanocrystals (SNCs), and chitin nanocrystals (ChNCs). We introduce the applications of PNs as stabilizers, adsorbents, film-forming materials, gel materials, disintegrants, and ointment matrices. We focus on the advantages of PNs to improve mechanical properties, thermal stability, therapeutic effect, biocompatibility, and release of active pharmaceutical ingredients. We discuss regulatory issues of PNs. We finally propose the challenges and future perspectives of PNs as pharmaceutical excipients.